Components of stakeholder participation to create value in the banking industry in East Azerbaijan Agricultural Bank - Alireza Tagavi; Alireza Bafandeh Zendeh; Samad Aali (ارزش آفرینی در مدیریت کسب و کار)
The purpose of this research is to examine the components of stakeholder participation to create value in the banking industry (the case study of East Azerbaijan Agricultural Bank). This research is developmental in terms of the goal, descriptive-exploratory in terms of the type of method, qualitative in terms of the method of collecting data, and meta-synthesis approach in terms of the method of conducting the research. The statistical population of the research includes 20 experts in the field of banking and stakeholder behavior analysis. The results showed that by using the scientific method of meta-synthesis and by reviewing published articles, the articles that dealt with the topic of business process integration were analyzed, and based on 27 selected articles, 37 indicators were extracted. In this study, 1009 articles and related researches in reputable journals were selected from citation profiles in the period before 2020. Finally, 11 cases were evaluated and identified, and the final framework was confirmed and identified by applying the total opinions of the experts, the components and indicators of the stakeholders' participation as 1- activity 2- resources 3- input/output 4- goal 5- time 6- technology 7- Laws 8- Beneficiaries (owner, executive, customer, and supplier). Extended Abstract Introduction If organizations want to be successful in the long term, they should prioritize the needs and expectations of stakeholders. Stakeholders have right expectations and demands that should be taken into account. Therefore, the interaction and proper management of stakeholders should be an essential part of the management tasks of organizations, so that the management of public issues is defined as responding to the diverse stakeholders of organizations (Goldar et al, 2017). The need for stakeholder theory has been widely highlighted to develop sound strategies for a large organization. However, there is still a lack of popular visualization and application tools, and no unique approach is available to identifying and engaging stakeholders (Regge et al, 2018). In the complex and turbulent environment of the competitive market, organizations try to create a suitable position in the eyes of customers by providing distinct value propositions to customers. Meanwhile, an organization that is able to create a special value in the minds of customers will have a competitive advantage. This has prompted organizations to focus on the needs and demands of customers to supply special and distinctive products and services. No organization in the current era can satisfy customers by only using its special capabilities and facilities. Organizations are seeking to provide different products and services to customers by cooperating and participating with each other. In addition, organizations consider themselves responsible for their stakeholders and try to provide their desired value (Rahman Sarasht & Sheykhi, 2019). About the main nature of value creation in different stages of the value creation process, according to some researchers, potential value is hidden in the customer value statement of companies and organizations, and companies and organizations present to customers (Kikha et al, 2022). This hidden value is hidden in the essence of stakeholders' resources, which is used in the design of customer value options because it is not yet presented to customers in the real market environment and in the offers of companies and organizations. This is despite the fact that the scope of the customer's point of view is located where the hidden value of the company's and organization's market offers are objectified (Milles, 2017). Therefore, according to the issues raised, the present study intends to answer the question: what are the components of stakeholders' participation to create value in the banking industry in East Azerbaijan Keshavarzi Bank? Theoretical Framework Stakeholder The word "stakeholder" was used for the first time by the Stanford Research Institute. After the emergence of stakeholder thinking in this institution, for the first time in a report presented on planning in 1963 (Slinger, 1997), the Stanford Research Institute defines stakeholders as "people without whose support the organization would cease to exist." (Mainardes, 2011). Creating value The old view states that suppliers sell products or provide services; and customers buy them (Carroll & Buchholtz, 2006). But now, customers have the ability to communicate with manufacturers in each of the production stages, from design to its supply. This type of communication, as a mutual process, should result learning in both parties. In the other word, based on new approaches, customers and suppliers will have the possibility to create common value by cooperating with each other. Creating shared value is a type of marketing plan or business plan that emphasizes the creation and successive recognition of shared values ​​of the organization and the company and customers. Sheykh Beglu et al, (2021) reviewed the presentation of the stakeholder participation model in public policy making in the health system. The findings showed that by means of the theme analysis method, the theme network of factors affecting the participation of stakeholders was extracted with 103 basic themes, 20 organizing themes, and 5 inclusive themes. Then, by applying structural-interpretive modeling and establishing pairwise relationships, relationships between overarching themes were discovered and prioritized in four levels. As a result, the final model represents the levels of the framework of stakeholder participation in public policy, including the factors that form the basis of stakeholder participation, the conditions of interaction with stakeholders, the influencing factors of stakeholders, the operational conditions of stakeholder participation, and the results and consequences of stakeholder participation. Kajuri et al, (2021) examined the presentation of the value creation model for bank customers in the process of co-creation of brand value by bank customers (the case study of Shahr Bank). The results showed that the dimensions of the model include customer motivation, customer value, organizational factors, customer experience, customer loyalty and customer mental image; and the model has a good fit. Research methodology This research is developmental in terms of the goal, descriptive-exploratory in terms of the type of method, qualitative in terms of the method of collecting data, and meta-synthesis approach in terms of the method of conducting the research. The statistical population of the research includes 20 experts in the field of banking and stakeholder behavior analysis. Research findings Using the scientific method of metasynthesis and reviewing the published articles, the articles that dealt with the topic of business process integration were analyzed; and 37 indicators were extracted based on 27 selected articles. In this study, 1009 articles and related researches in reputable journals were selected from citation profiles in the period before 2020. Finally, 11 cases were evaluated and identified, and the final framework was confirmed and identified by applying the total opinions of experts, components and indicators of stakeholder participation as 1- activity 2- resources 3- input / output 4- goal 5- time 6- technology 7- rules 8- stakeholders (owner, (executor, customer, supplier). Conclusion The current research was conducted with the aim of investigating the components of stakeholders' participation to create value in the banking industry (the case study of East Azerbaijan Keshavarzi Bank). According to the obtained results, the current research is in line with the results of Sheykh Beglu et al, (2021), Kajuri et al, (2021), Fattahi & Rasulizad (2020), Seddigh et al, (2020), Bernadette et al, (2019), Shahmandi & Purajam (2019), Barzwar (2019), Esser & McNeill (2018), and Rukman (2017). Sheykh Beglu et al, (2021) investigated the presentation of the stakeholder participation model in public policy making in the health system. The findings showed that by means of the theme analysis method, the theme network of factors affecting the participation of stakeholders was extracted with 103 basic themes, 20 organizing themes, and 5 inclusive themes. Then, by applying structural-interpretive modeling and establishing pairwise connections, relationships between overarching themes were discovered and prioritized in four levels. As a result, the final model represents the levels of the framework of stakeholder participation in public policy, including the factors that form the basis of stakeholder participation, the conditions of interaction with stakeholders, the influencing factors of stakeholders, the operational conditions of stakeholder participation, and the results and consequences of stakeholder participation. According to the obtained results, the following suggestions were presented: - Organizations should try to adjust the output of processes as much as possible for the formation of other processes, and this will be the basis for integration between processes as much as possible. - Organizations should act towards the integration of goals by having missions, goals, plans and strategies aligned in all processes. - Regarding the time component, as a component that has a special effect on processes and their implementation, as well as their integration, especially in today's fast-paced world, paying attention to the time required to implement processes, the time required to change business processes and the implemented work, the time that the business process works without errors and the time required to communicate between the processes should be taken into consideration. - Based on the indicators of process automation level and the amount of attention to technology integration management, it is possible to help the integration of business processes to a great extent.